Maternal Hemorrhage Quality Improvement Collaborative Lessons. Issue 6 (November 2016) - Lyndon, Audrey; Cape, Valerie
Abstract: Purpose: The purpose of this study was to describe user experience with implementation of an obstetric hemorrhage toolkit and determine the degree of implementation of recommended practices that occurred during a 31-hospital quality improvement learning collaborative. Study Design and Methods: This descriptive qualitative study included semistructured interviews with 22 implementation team leaders and review of transcripts from collaborative reporting calls recorded during the hemorrhage collaborative. Interviews included open-ended, closed, and ranking questions. Numeric responses were analyzed with descriptive statistics. Open-ended responses and call transcripts were analyzed thematically. Results: Each of the 10 core toolkit components was ranked as currently "implemented" or "implemented and sustained" by at least 77% of interviewees. Most core elements were deemed "critical to retain." Respondents found debriefing the most difficult element of the toolkit to implement and sustain. Organizational context was the overarching theme regarding factors facilitating or constraining implementation. This included organizational structure and culture, previous experience with quality improvement, resources, and clinician engagement. Nurses were deeply involved in implementation and "physician buy-in" was a frequently mentioned facilitator when present and barrier when absent. Clinical Implications: Greater understanding of and attention to organizational context and resources, greater appreciation for nursing involvement, and increased recognition of the role of organizational leadership are needed to facilitate widespread improvement initiatives in maternity care. Implementation science approaches may be useful in achieving national goals for maternal quality improvement and safety. Abstract : Obstetric hemorrhage is a leading cause of maternal death in the United States and the world. Organized collaborative efforts with representatives from all members of the perinatal team have been underway in the United States to reduce postpartum hemorrhage. The California Maternal Quality Care Collaborative (CMQCC) has been the leader in developing an obstetric hemorrhage toolkit that has been used by multiple hospitals and healthcare systems across the country. The first author of the CMQCC obstetric hemorrhage toolkit, Dr. Audrey Lyndon, and her colleague Valerie Cape, project coordinator, share their analysis of lessons learned from the collaborative.